The rise of China and its implications for economics and other developing countries: the significance of the Chinese social model. Issue 2 (4th May 2017) - Dunford, Michael
ABSTRACT: The rise of China is an important case of latecomer advantage that reflects a privilege of backwardness. As such, it affords an important example of the principle of uneven and combined development, and important lessons for other emerging countries. These lessons are many and include the importance of the grounding of economic models in supportive and capable institutional configurations.